Meningkatkan Hasil Belajar PPKn Dengan Menerapkan Pendekatan Pembelajaran Kontekstual (CTL) - Slamet Riyadi (Universitas Hamzanwadi, 2019)
This study aims to describe which improvements improve learning outcomes by increasing contextual spending on class VIII 5 of SMP Negeri 1 Pringgasela. The type of research used in this study is classroom action research. This research was conducted at SMP Negeri 1 Pringgasela. The action phase is carried out in 2 cycles and each cycle consists of 2 meetings while meeting 1 implementation of the action and 2 cycle cycles. The results of this study can be concluded that the increase in student learning outcomes in the first cycle was 67.86% and the second cycle was 85.71%, while the increase in the ratio in the second cycle was 17.85%, this means that it is related to the application of simultaneous contextual learning support can improve student learning outcomes on citizenship subjects. This relates to the results of observations of student learning activities in the